Cross-Border Issues in Energy Trade in the CIS Countries - Shiells, Clinton (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2002)
This paper explores from a regional perspective the distorted nature of trade in energy products within the CIS countries. The persistence of pricing distortions, barter arrangements, and discriminatory access to pipelines, as well as failure to honor contracts, has disrupted and distorted energy exports to non-CIS countries, undermined energy sector reforms, and distorted investment decisions. The paper focuses on cross-border issues as an integral component of the wider problem of inefficient energy use within the CIS. Several policy recommendations are proposed, including measures to foster greater competition, reduce state involvement, and promote regional cooperation.